2004
DOI: 10.1093/jee/97.2.475
|View full text |Cite
|
Sign up to set email alerts
|

Behavior and Pollination Efficiency of Nannotrigona perilampoides (Hymenoptera: Meliponini) on Greenhouse Tomatoes (Lycopersicon esculentum) in Subtropical México

Abstract: The acclimation, foraging behavior, and pollination efficiency of stingless bees of the species Nannotrigona perilampoides Cresson were evaluated in tomato (Lycopersicon esculentum Mill.) plants cultivated in two greenhouses. The greenhouses were divided into three areas of 16 m2, and one of the following treatments was used for pollination: stingless bees (SB), mechanical vibration (MV), and no pollination (NP). Observations were conducted once a week from 0800 to 1600 hours during 2 mo. The acclimation of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
2
7

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(55 citation statements)
references
References 20 publications
2
44
2
7
Order By: Relevance
“…The present study extends previous work that demonstrates the feasibility of using local pollinator species for agricultural greenhouse pollination (Hogendoorn et al, 2000(Hogendoorn et al, , 2006Cauich et al, 2004;Del Sarto et al, 2005). A major obstacle to the commercial use of native pollinators in agriculture is the need to mass-rear them, rather than collect them from nature.…”
Section: Discussionsupporting
confidence: 79%
“…The present study extends previous work that demonstrates the feasibility of using local pollinator species for agricultural greenhouse pollination (Hogendoorn et al, 2000(Hogendoorn et al, , 2006Cauich et al, 2004;Del Sarto et al, 2005). A major obstacle to the commercial use of native pollinators in agriculture is the need to mass-rear them, rather than collect them from nature.…”
Section: Discussionsupporting
confidence: 79%
“…If there is concern about the dangers adhering to importation, both the government and the farmers should invest in research. Indeed, several studies have been performed to date (Hogendoorn et al, 2000(Hogendoorn et al, , 2006Estay et al, 2001;Sabara and Winston, 2003;Cauich et al, 2004;Higo et al, 2004;Hogendoorn, 2004;Sabara et al, 2004;Del Sarto et al, 2005) and have shown that the major obstacle is the mass-rearing of alternative pollinators. As long as this aspect has not been overcome, there is a high risk that nature will be robbed again of native bees.…”
Section: Balancing Ecological and Economic Argumentsmentioning
confidence: 99%
“…comm.). Even more recently, tomatoes have been pollinated successfully using the stingless bee species, Nannotrigona perilampoides (Cauich et al, 2004). The authors note, however, that more research is needed on the biology of this latter species, before it can be used commercially.…”
Section: Introduction Of Non-native Speciesmentioning
confidence: 99%
“…For example, honeybees, and some species of ants and wasps maintain a high and stable nest RH (Bollazzi and Roces, 2010;Ellis et al, 2010;Human et al, 2006;Weidenmüller et al, 2002). A mechanism for regulating a higherthan-ambient hive humidity is relatively straightforward as an inhabited hive should accumulate a higher RH than the environment because of retention of respiratory and cutaneous water lost by the inhabitants (Woods and Smith, 2010) and water can be introduced into a hive through a number of avenues such as bees carrying in nectar and water (Cauich et al, 2004;Kühnholz and Seeley, 1997;Lindauer, 1955a). Furthermore, given the small entrance to the hive relative to its volume (Fig.…”
Section: Hive Regulationmentioning
confidence: 99%